2014
DOI: 10.1016/j.biortech.2013.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestate as substrate for microalgae culture: The role of ammonium concentration on the microalgae productivity

Abstract: In spite of the increasing interest received by microalgae as potential alternatives for biofuel production, the technology is still not industrially viable. The utilization of digestate as carbon and nutrients source can enhance microalgal growth reducing costs and environmental impacts. This work assesses microalgal growth utilizing the liquid phase of anaerobic digestate effluent as substrate. The effect of inoculum/substrate ratio on microalgal growth was studied in a laboratory batch experiment conduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(113 citation statements)
references
References 32 publications
7
101
2
3
Order By: Relevance
“…Several research studies were already performed with microalgal growth in wastewaters from different sources: (i) domestic wastewater [19][20][21]; (ii) anaerobic digestion wastewater [22][23][24]; (iii) livestock wastewater [25][26][27]; and (iv) agro-industrial wastewater [28,29]. In almost all studies, microalgae were able to efficiently remove the monitored nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies were already performed with microalgal growth in wastewaters from different sources: (i) domestic wastewater [19][20][21]; (ii) anaerobic digestion wastewater [22][23][24]; (iii) livestock wastewater [25][26][27]; and (iv) agro-industrial wastewater [28,29]. In almost all studies, microalgae were able to efficiently remove the monitored nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Prajapati et al (2014a) showed the feasibility of such a closed-loop process, using different concentrations of digestate for the cultivation of Chroococcus sp. Uggetti et al (2014) …”
Section: The Closed-loop Processmentioning
confidence: 97%
“…Ammonium (NH 4 + ) and phosphate (PO 4 3 − ) ions were quantified using an ion chromatography system (ICS 3000 Dionex, USA), as described elsewhere [29].…”
Section: Chemical Analysismentioning
confidence: 99%